How Right Are Multiple Sclerosis Patients in Fear of Falling? A Comparative Study - Tekın, Fatıh; Bılek, Furkan (My University, 2022)
Objectives: The aim of this study was to investigate the factors underlying the fear of falling in Multiple Sclerosis (MS) patients and to determine the share of physical and psychological components in this fear.Materials and Methods: Patients between the ages of 18-65 years, diagnosed with Relapsing-Remitting form of MS were included in the study. Timed Up and Go Test (TUG) was used to assess gait functions and balance skills of patients during gait, Berg Balance Test (BBT) to assess balance skills in general, Fall Efficacy Scale-International (FES-I) to assess fear of falling, and Expanded Disability Status Scale (EDSS) to assess MS severity of the patients.Results: Forty-four patients (F:32 M:12) diagnosed with MS, with a mean age of 37.23±9.67 years, were included in our study. There was a statistically significant, positive and moderate correlation between the fear of falling and the number of attacks in the last 1 year (r=0.433, p=0.039), a statistically significant, positive and high-level correlation between fear of falling and falling history in the last 1 year (r=0.912, p=0.001), disability status (r=0.940, p=0.001) and TUG test (r=0.901, p=0.001) and a significant, negative and high-level correlation between fear of falling and balance skills (r=-0.944, p=0.001). According to the regression analysis, while the effects of falling history (p=0.043), BBT (p=0.025), TUG (p=0.004), and EDSS (p=0.007) on FES-1 were significant, the effect of TPLA was insignificant (p>0.05).Conclusion: Patients with MS are right about their fear of falling in parallel with their disability and balance-gait skills. However, this relationship is bidirectional, and the fear of falling has the potential to increase these limitations even more in MS patients whose functional activities are already restricted or going to be restricted.
Keywords: Gait; fear of falling; multiple sclerosis; balance